Evaluasi Penerapan Good Governance dalam Pengelolaan Dana Desa: Studi Kasus di Desa Daenaa Kecamatan Limboto Barat - Marshanda Eka Putri Dukalang; Rio Monoarfa; Muzdalifah Muzdalifah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to evaluate the application of good governance principles in the management of Village Funds in Daenaa Village, West Limboto District, Gorontalo Regency. The research method used is qualitative research with a case study approach. Data were obtained through observation, interviews, and documentation. Research informants consisted of the Village Head, Village Secretary, Village Treasurer, Head of the Village Consultative Body (BPD), and the Daenaa Village community. Data analysis techniques used the Miles and Huberman model which includes data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that the application of good governance principles in the management of Village Funds in Daenaa Village has been running quite well. Transparency is realized through village deliberations, information boards, budget billboards, and regular meetings with the community. Accountability is implemented through the preparation of realization reports, financial reports, and periodic activity reports in accordance with applicable regulations. Community participation has been involved in the planning and implementation of village development programs. In addition, the use of Village Funds has been directed to the priority needs of the community, thus supporting the effectiveness and efficiency of budget management. However, obstacles remain, including a lack of public understanding of Village Fund management information and suboptimal community participation. The conclusion of this study indicates that the application of good governance principles in Village Fund management in Daenaa Village has been quite successful, but further improvements are needed through strengthening information transparency, enhancing the quality of public communication, and optimizing community involvement in the monitoring and implementation of village development.